2020
DOI: 10.1055/s-0040-1718403
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Hemorrhage Risk Associated with Novel COVID-19 Diagnosis from a Single-Institution Cohort in the United States

Abstract: Objective The study aimed to compare the quantitative blood loss (QBL) and hemorrhage-related outcomes of pregnant women with and without a coronavirus disease 2019 (COVID-19) diagnosis. Study Design This retrospective cohort study of all live deliveries at Boston Medical Center between April 1, 2020 and July 22, 2020 compares the outcomes of pregnant women with a laboratory-confirmed COVID-19 positive diagnosis and pregnant women without COVID-19. The primary outcomes are QBL and obstetric hemorrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
1
21
0
3
Order By: Relevance
“…Postpartum haemorrhage (PPH), as defined by a blood loss > 500 mL, was the leading postpartum complication with a rate of 14%. Several studies reported PPH have investigated such outcome in pregnant women with COVID-19 [30] , [31] . A rate of postpartum haemorrhage (> 1000 mL) of 9% was observed in a cohort of 64 pregnant women with COVID-19 [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postpartum haemorrhage (PPH), as defined by a blood loss > 500 mL, was the leading postpartum complication with a rate of 14%. Several studies reported PPH have investigated such outcome in pregnant women with COVID-19 [30] , [31] . A rate of postpartum haemorrhage (> 1000 mL) of 9% was observed in a cohort of 64 pregnant women with COVID-19 [30] .…”
Section: Discussionmentioning
confidence: 99%
“…This rate reached 13% in the severe disease group (n = 44) and 6% in the critical disease group (n = 20) [30] . Nevertheless, in a retrospective cohort study which included 53 pregnant women with COVID-19 and 760 non-COVID-19 pregnant women, it was reported that deliveries associated with COVID-19 were not at increased risk for increased blood loss or obstetric haemorrhage compared with deliveries without COVID-19 [31] .…”
Section: Discussionmentioning
confidence: 99%
“…Les cas de COVID-19 ont été confirmés par un test de dépistage par PCR. Vingt-huit études portaient sur une infection par le SRAS-CoV-2 confirmée durant la grossesse comparativement à l'absence d'infection [11][12][13]15,22,[27][28][29][30][31][32]34,35,37,[39][40][41][42][43][44][45][47][48][49][50][51]53,54 . Douze études ont mis en parallèle la COVID-19 symptomatique et asymptomatique [7][8][9][10][11][12][13][14][15]46,48,52 .…”
Section: Résultatsunclassified
“…Adhikari et al 48 Ahlberg et al 43 Brandt et al 22 Erol et al 50 Gulersen et al 29 Jering et al 53 Martínez-Perez et al 18 Patberg et al 41 Pirjani et al 37 Wang et al 39 Yang et al 42 Yazihan et al 47 Zhang et al 40 Total…”
Section: B éTude Ou Sous-groupementioning
confidence: 99%
See 1 more Smart Citation